C15 DOES THE DISTANCE BETWEEN RESIDENCY AND IMPLANTING CENTER AFFECT THE OUTCOME OF PATIENTS SUPPORTED BY LEFT VENTRICULAR ASSIST DEVICE? A MULTICENTER ITALIAN STUDY ON RADIAL MECHANICALLY ASSISTED CIRCULATORY SUPPORT (MIRAMACS) ANALYSIS. (18th May 2022) - Lechiancole, A; Loforte, A; Trumello, C; Scandroglio, M; Gliozzi, G; Comisso, M; Iacovoni, A; Terzi, A; Maiani, M; Musumeci, F; De Bonis, M; Pacini, D; et al.
Abstract: Background: Patients with LVAD require continuous monitoring and care, and since Implanting Centers (IC) are more experienced in managing LVAD patients than other health care facilities, the distance between patient residency and IC could negatively affect the outcomes. Methods: Data of patients discharged after receiving a LVAD implantation between 2010 and 2021 collected into the MIRAMACS database were retrospectively analyzed. The population was divided into two groups: A (n = 175) and B (n = 141), according to a distance between patient residency and IC ≤ or >of 90 miles. The primary end–point was freedom form Adverse Events (AEs), a composite outcome composed by death, cerebrovascular accident, hospital admission because of GI bleeding, infection, pump thrombosis or right ventricular failure. Secondary end–points were incidences of mortality and complications. All patients were followed–up regularly, according to participating centers protocols, by means of clinical visits, telemonitoring and local care–sharing. Results: Baseline clinical characteristics and indications for LVAD did not differ between the two groups (Figure 1 ). Mean duration of support was 25.5±21 months for Group A and 25.7±20 months for Group B (p = 0.79). At 3 years, freedom from AEs was similar between Group A and B (p = 0.32, Figure 2 ), and there were no differences in rates of mortality and LVAD–related complications (Figure 2 ). Conclusions: Distance from the IC does not represent a barrier to successful outcome, as long as regular and continuous follow–up is provided. Telemonitoring could offer several benefits, including early detection of complications and continuous evaluation of patient conditions and data of the pump. Moreover, it seemed to reduce the patient anxiety related to the device, increasing direct communication with the VAD–team. On the other hand, shared health programs with local facilities remains an attractive way to follow–up patient, provided that LVAD specific resources and trained staff are available. The dissemination of LVAD–specific care knowledge is also important to face urgent or emergent needs in the rapidly enlarging population of LVAD patients, by empowering local healthcare facilities.